2010
DOI: 10.1111/j.1475-5661.2010.00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotional, embodied and affective geographies of alcohol, drinking and drunkenness

Abstract: This paper develops dialogue between geographers' engagement with emotion, embodiment and affect, and geographical research on alcohol, drinking and drunkenness. In doing so, we focus on the long-running 'moral panic' relating to alcohol-related violence, disorder and drunken behaviour in urban public space. We argue there has been an ontological and epistemological impasse in 'alcohol studies' between approaches that have considered the biological, physiological and psychological impacts of alcohol consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
139
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(147 citation statements)
references
References 38 publications
3
139
1
4
Order By: Relevance
“…Retail practices and outlet types have been the focus of previous research from various disciplines including geography, anthropology and sociology (Bøhling, 2015;Chatterton and Hollands, 2003;Eldridge and Roberts, 2008;Jayne et al, 2010;Shaw, 2014;Taylor and Falconer, 2014;Valentine, 2007): such research could inform evaluations seeking to examine changes in the alcohol environment (Gruenewald et al, 2002). The relationship between outlet type and area deprivation could also aid understanding of how changes to the alcohol environment relate to health inequalities and urban regeneration goals (Shortt et al, 2015).…”
Section: Research Implicationsmentioning
confidence: 99%
“…Retail practices and outlet types have been the focus of previous research from various disciplines including geography, anthropology and sociology (Bøhling, 2015;Chatterton and Hollands, 2003;Eldridge and Roberts, 2008;Jayne et al, 2010;Shaw, 2014;Taylor and Falconer, 2014;Valentine, 2007): such research could inform evaluations seeking to examine changes in the alcohol environment (Gruenewald et al, 2002). The relationship between outlet type and area deprivation could also aid understanding of how changes to the alcohol environment relate to health inequalities and urban regeneration goals (Shortt et al, 2015).…”
Section: Research Implicationsmentioning
confidence: 99%
“…Conventional campaigns also tend to focus on individual responsibility and ignore the group-based social nature of drinking (de Visser et al, 2013;Fry, 2011;Harrison et al, 2011;Hutton, 2012;Jayne et al, 2010;Szmigin et al, 2011). Therefore, campaigns that target individual harms arising from HED may be dismissed as irrelevant, particularly given that many are perceived to employ a patronizing, paternalistic, or preaching tone (de Visser et al, 2013).…”
Section: Young People and Alcoholmentioning
confidence: 99%
“…Therefore, campaigns that target individual harms arising from HED may be dismissed as irrelevant, particularly given that many are perceived to employ a patronizing, paternalistic, or preaching tone (de Visser et al, 2013). Peer group drinking and drunkenness are important aspects of the social lives of many young people: the individual experience of intoxication is often accompanied by enhanced feelings of togetherness (Brown & Gregg, 2012;de Visser et al, 2013;Fry, 2011;Jayne et al, 2010;Livingstone, Young & Manstead, 2011;MacNeela & Bredin, 2011;Szmigin et al, 2011;Thurnell-Read, 2011). Furthermore, recent qualitative research has revealed that many young people believe that some negative aspects of drinking -such as caring for drunk friends, being cared for when drunk, and suffering through hangovers with friends -offer opportunities for strengthening interpersonal bonds (de Visser et al, 2013).…”
Section: Young People and Alcoholmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is a wealth of geographical literature about emotion (Davidson et al 2007;Jayne et al 2010;Smith et al 2011;Thien 2005), relatively few studies consider the emotional and experiential aspects of transport use for disabled (young) people. This suggests that understandings of transport exclusion and transport disability are at present partial.…”
Section: Introductionmentioning
confidence: 99%